Institutionalized reason the jurisprudence of Robert Alexy - Klatt, Matthias (Oxford : Oxford University Press, 2012)
This volume brings together leading figures from Anglo-American and German legal philosophy and constitutional theory to examine themes from the influential work of Robert Alexy. The topics covered include the nature of law and legal reasoning, and the nature of constitutional rights.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Alexy, Robert; Jurisprudence; Law -- Philosophy; Civil rights